2011
DOI: 10.1037/a0021193
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering vocational interests for personnel selection: The validity of an interest-based selection test in relation to job knowledge, job performance, and continuance intentions.

Abstract: Although vocational interests have a long history in vocational psychology, they have received extremely limited attention within the recent personnel selection literature. We reconsider some widely held beliefs concerning the (low) validity of interests for predicting criteria important to selection researchers, and we review theory and empirical evidence that challenge such beliefs. We then describe the development and validation of an interests-based selection measure. Results of a large validation study (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 113 publications
(142 reference statements)
2
101
0
2
Order By: Relevance
“…They also found that validity was higher when the interest measure related to the target job (another form of contextualization) and when a combination of interests was used to predict job performance. In an empirical study, Van Iddekinge et al (2011a) developed an interest measure targeted to military jobs. Estimated crossvalidity of multiple correlations of interest measures with five criteria ranged from .13 to .31.…”
Section: Miscellaneous Contributionsmentioning
confidence: 99%
“…They also found that validity was higher when the interest measure related to the target job (another form of contextualization) and when a combination of interests was used to predict job performance. In an empirical study, Van Iddekinge et al (2011a) developed an interest measure targeted to military jobs. Estimated crossvalidity of multiple correlations of interest measures with five criteria ranged from .13 to .31.…”
Section: Miscellaneous Contributionsmentioning
confidence: 99%
“…Furthermore, motivation as assessed by general self-efficacy plays a vital role in the prediction of professional success (Abele & Spurk, 2009;Abele, Stief, & Andrä, 2000;Judge & Bono, 2001). For the predictive power of (professional) interests regarding job success two rather recent meta-analyses are available: Van Iddekinge, Putka and Campbell (2011) showed that (mostly Holland's RIASEC) interest scales are good at predicting training performance (.26), and less so, but still they are valid for intended and actual turnover (.19 and .15), whereas the prediction of job performance was lowest (.14). These results hold for single interest scales that come mostly from the general RIASEC model, but prediction can be improved through the use of special scales designed to measure interests for particular jobs.…”
Section: Predictive Validity Of Abilities Personality and Vocationamentioning
confidence: 99%
“…Taking just three types of individual difference variables commonly measured in IPAs—occupational interests, abilities, and personality (see Lowman, 1991, 1993)—there is at present greater validation literature within each of these domains than across them. For example, Lowman and Carson (in press) demonstrate the strong and persistent validity for career and work performance issues and reliability of measures from three separate domains: occupational interests (see also Van Iddekinge, Putka, & Campbell, 2011), general intelligence and some of the specific abilities (e.g., Lowman, 1991), and selected personality variables (e.g., Rothstein & Goffin, 2006). However, they note the paucity of what I’ve termed interdomain research, that is, research aimed at establishing the relationships across the three domains of interests, abilities, and personality.…”
Section: What Should Be Measured In Ipa?mentioning
confidence: 99%